(untitled) (Research, Society and Development, 2021)
The objective of this work was to estimate direct public spending on COPD and lung, bronchial and tracheal cancer in Altamira city, in the Brazilian Amazon region, between the years 2017 to 2020. This is a cross-sectional study based on official and secondary data from the Information System Hospitals of the Unified Health System (SIH/SUS), provided by the Informatics Department of the Unified Health System (DATASUS) from 2017 to 2020 for Altamira (PA). The spent on hospital care for residents of the municipality of Altamira (PA) related to COPD and lung, trachea, bronchial cancer in other cities was R 129,056.28. The cost to the government in hospitalizations in the municipality as a result of hospitalizations motivated by these pathologies was R 148,753.7. The early death, emotional suffering and significant avoidable financial costs are effects of these diseases. So, early diagnosis, health education practices and health care support against smoking are fundamental to mitigate the economic impact of these diseases on the Brazilian public health system and to promote an improvement in the life quality of Altamira’s population.